Pemeriksaan Kesehatan dan Terapi Komplementer di Kelurahan Murni Kecamatan Danau Sipin Kota Jambi - Fithriyani Fithriyani; Rahmi Dwi Yanti (Jurnal Abdimas Kesehatan (JAK), 2021)
Age, poverty and lack of knowledge about the use of health services are a combination of risk factors that can make their health more vulnerable. The area of Murni Village, Danau Sipin District, Jambi City, 50.28% of the community is the stage of adulthood, namely 19-55 years. From these data, it is detected that they have a history of hypertension, rheumatism, diabetes mellitus and gastritis, but the exact incidence cannot be estimated. distribution of these health problems, it is necessary to carry out routine and specific health checks so that health problems can be detected in the pure village residents. The target of this activity is the elderly in RT 3, Murni, namely by conducting health examination activities which include measurement of blood pressure, blood sugar, and BMI as well as socialization of complementary therapy to cadres and local residents. Based on the results of blood pressure checks obtained from 35 people, 37% (13) people with high blood pressure and 22 (63%) people with blood pressure within normal limits. Examination of high blood sugar 2 (6%), 32 (91%) normal and 1 (3%) with low blood sugar. The status of blood pressure in the community in RT 03 Kelurahan Murni is a small part with high blood pressure and the status of blood sugar levels in the community in RT 03 Kelurahan Murni is mostly with normal blood sugar